Zebrafish model for screening tool in pharmacognosy - Khatib, Alfi (2019)
New definition of pharmacognosy includes system biology and data pooling as part of this branch of science. As consequence, a rapid, accurate, and cheap animal model is required. In this presentation, our effort to develop a new diabetes model is discussed. The objectives of this study were per the following: to develop a type 1 diabetic adult zebrafish model through chemical induction, and to evaluate the anti-diabetic activity of Psychotria malayana leaf extract on the developed type 1 diabetic adult zebrafish. The result exhibited that the new developed model is valid to be used for testing of anti-diabetic agent. The diabetic model can be last for 1 week which is sufficient for herbal research.